(untitled) (Academicia Globe: Inderscience Research, 2022)
Invasive mycoses are significant causes of morbidity and mortality in different immunocompromised patients. Candida spp., Aspergillus spp. and Cryptococcus neoformans are main pathogens in these patients. Several new diagnostic methods and systemic antifungal agents have been approved for clinical use in last ten years. This review focuses on modern recommendation for diagnosis and treatment of invasive mysoses.